Polyurethane oligomer, preparation method thereof and UV viscosity-reducing adhesive tape

By using special polyurethane oligomers in UV adhesive tape, the problem of excessive adhesion after lighting of existing UV adhesive tape is solved, and high adhesion before lighting and low adhesion after lighting is achieved. The effect of force meets the needs of special use scenarios.

CN119431729APending Publication Date: 2025-02-14SHENZHEN INST OF ADVANCED ELECTRONICS MATERIALS

Patent Information

Application Number
CN202411542480.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing UV adhesive tape has a strong bonding force after lighting, which cannot meet the special needs of high bonding during cutting or use.

Method used

Using a polyurethane oligomer whose synthetic raw materials include diisocyanate, diol, hydroxy acrylate, catalyst and polymerization inhibitor, polyurethane oligomer with multifunctionality is prepared by a specific preparation method for preparing UV Reduced adhesive tape.

Benefits of technology

The adhesive force of UV adhesive tape before lighting is improved, and the adhesive force is reduced after lighting, making it below 2.3N/25mm, meeting the needs of special use scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431729A_ABST
    Figure CN119431729A_ABST
Patent Text Reader

Abstract

The invention discloses a polyurethane oligomer, a preparation method thereof and a UV viscosity-reducing adhesive tape, and relates to the technical field of advanced materials. The polyurethane oligomer is prepared from the following synthetic raw materials in parts by mass: 25 to 40 parts of diisocyanate, 10 to 20 parts of dihydric alcohol, 40 to 60 parts of propylene hydroxyl ester, 0.04 to 0.08 part of a catalyst and 0.04 to 0.08 part of a polymerization inhibitor, the propylene hydroxyl ester comprises pentaerythritol triacrylate. According to the embodiment of the invention, the polyurethane oligomer synthesized from the specific raw materials is added into the UV viscosity-reducing adhesive, so that the adhesive strength of the UV viscosity-reducing adhesive before illumination is improved, the illuminated UV viscosity-reducing adhesive has relatively small adhesive strength, and the adhesive strength of the illuminated UV viscosity-reducing adhesive is 2.3 N / 25mm or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of advanced material technology, and in particular to a polyurethane oligomer and a preparation method thereof, and a UV anti-viscosity tape. Background Art

[0002] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.

[0003] In recent years, with the development of semiconductor cutting and cutting of hard materials such as glass and substrates, new demands have been put forward for UV anti-adhesive tapes. In some special use scenarios, UV anti-adhesive tapes need to have high adhesion during cutting or use, and the adhesion after UV light exposure is low (for example, less than 3N / 25mm), while the UV anti-adhesive tapes on the market have the problem of high adhesion after light exposure. Summary of the invention

[0004] In view of this, the present application provides a polyurethane polymer and a preparation method thereof, and a UV anti-viscosity tape, aiming to improve the technical problem that the existing UV anti-viscosity adhesive has a large adhesion after exposure to light.

[0005] In a first aspect, an embodiment of the present application provides a polyurethane polymer, wherein the raw materials for synthesizing the polyurethane polymer include, by mass: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of hydroxy acrylate, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of inhibitor; the hydroxy acrylate includes pentaerythritol triacrylate.

[0006] In some embodiments of the present application, the number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4.

[0007] In some embodiments of the present application, the weight average relative molecular mass of the polyurethane oligomer is 900 g / mol to 3000 g / mol.

[0008] In some embodiments of the present application, the double bond content of the polyurethane oligomer is 0.3 mol / 100 g to 0.6 mol / 100 g.

[0009] In some embodiments of the present application, the solid content of the polyurethane oligomer is 40% to 60%.

[0010] In some embodiments of the present application, the diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate; and / or

[0011] The diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol; and / or

[0012] The hydroxy acrylate includes at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate, pentaerythritol triacrylate, etc.; and / or

[0013] The catalyst comprises at least one of triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, and zinc naphthenate; and / or

[0014] The polymerization inhibitor includes at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

[0015] A second aspect of the present invention provides a method for preparing a polyurethane oligomer, the method comprising the following steps:

[0016] Add diisocyanate, catalyst and solvent into the reaction kettle, then add diol dropwise for 1.5 to 3 hours, keep warm for 0.5 to 2 hours after the addition, and control the reaction temperature at 40 to 50°C;

[0017] Add hydroxy acrylate and polymerization inhibitor to the reaction kettle, the addition time is 0.5 to 1 hour, keep warm for 5 hours to 10 hours after the addition is completed, and then raise the temperature to 50°C to 65°C until the reaction is completed.

[0018] In some embodiments of the present application, the step of heating the temperature to 50° C. to 65° C. until the reaction is complete comprises: taking the reaction solution for infrared analysis at intervals, and determining the completion of the reaction based on characteristic peaks; or

[0019] The reaction solution was taken for -NCO value titration. If the titration result was ≤0.5%, the reaction was considered complete.

[0020] A third aspect of the present application provides a UV anti-viscosity tape, wherein the UV anti-viscosity tape comprises the polyurethane oligomer.

[0021] In some embodiments of the present application, the UV anti-viscosity tape includes a UV anti-viscosity adhesive and a substrate film. The UV anti-viscosity adhesive includes an acrylate resin, a thermal curing agent, a photoinitiator and the polyurethane polymer. By mass, the acrylate resin: the polyurethane polymer: the thermal curing agent: the photoinitiator is (60 to 80): (18 to 38): (0.5 to 1): (0.8 to 1.8).

[0022] In some embodiments of the present application, the UV viscosity-reducing adhesive does not include a reactive diluent or a reactive monomer.

[0023] In some embodiments of the present application, the synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers; the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; wherein the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60~70): (20~30): (0.5~1.5): (0.5~1.5): (6~9). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 Schematic diagram of the reaction mechanism of the polyurethane oligomer provided in the examples of the present application. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0028] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0029] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0030] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0032] UV adhesive tape is a tape that has high adhesion before light exposure, but greatly reduces adhesion after light exposure. It is widely used in medical, display, semiconductor and other fields due to its excellent transparency and adhesion. After a short period of light exposure, an interpenetrating polymer network structure is formed inside the UV adhesive tape. This structure changes the fluidity, cross-linking density, free volume and surface energy of the system, thereby reducing the adhesiveness and peeling strength of the tape.

[0033] In recent years, with the development of semiconductor cutting and cutting of hard materials such as glass and substrates, new demands have been put forward for UV anti-adhesive tapes. In some special use scenarios, UV anti-adhesive tapes need to have high adhesion during cutting or use, and the adhesion after UV light exposure is low (for example, less than 3N / 25mm), while the UV anti-adhesive tapes on the market have the problem of high adhesion after light exposure.

[0034] In view of this, an embodiment of the present application provides a UV viscosity-reducing adhesive, which includes a polyurethane oligomer. Specifically, the raw materials for synthesizing the polyurethane oligomer include: 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of hydroxy acrylate, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of inhibitor; the hydroxy acrylate includes pentaerythritol triacrylate. Taking isophorone diisocyanate as the diisocyanate as an example, the schematic diagram of the preparation process of the polyurethane oligomer is shown as follows: Figure 1 shown.

[0035] In the embodiment of the present application, a polyurethane polymer synthesized from specific raw materials is added to the UV viscosity-reducing adhesive, which is beneficial to improving the adhesion of the UV viscosity-reducing adhesive before illumination, and making the UV viscosity-reducing adhesive have a smaller adhesion after illumination. The adhesion of the UV viscosity-reducing adhesive after illumination is below 2.3N / 25mm.

[0036] In some embodiments of the present application, the polyurethane oligomer has multifunctionality. Specifically, the number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4. Exemplarily, the number of double bonds in the molecular structure of the polyurethane oligomer can be 4, 5 or 6, etc., which are not limited here. It is understandable that the number of double bonds in the molecular structure of the polyurethane oligomer and the double bond content of the polyurethane oligomer can be adjusted by controlling the composition and proportion of hydroxy acrylate. Preferably, the double bond content of the polyurethane oligomer is 0.3mol / 100g to 0.6mol / 100g. In this way, it is conducive to improving the adhesion of the UV viscosity-reducing adhesive before illumination, and making the UV viscosity-reducing adhesive after illumination have a smaller adhesion.

[0037] In some embodiments of the present application, the weight average relative molecular mass of the polyurethane oligomer is between 900 g / mol and 3000 g / mol. Further, the weight average relative molecular mass of the polyurethane oligomer is between 900 g / mol and 1200 g / mol. In this way, it is beneficial to improve the adhesion of the UV viscosity-reducing adhesive before illumination, and make the UV viscosity-reducing adhesive have a smaller adhesion after illumination.

[0038] Furthermore, the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate and the like.

[0039] Further, the diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol. Exemplarily, the diol is polyethylene glycol 200. Polyethylene glycol 200 has good solubility in most solvents and low cost, which is conducive to reducing the preparation cost of polyurethane oligomers.

[0040] Furthermore, the hydroxy acrylate further comprises at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, trimethylolpropane diacrylate, etc. Thus, by making the hydroxy acrylate include a combination of multiple monomers with different numbers of double bonds, the number of double bonds in the molecular structure of the polyurethane oligomer and the double bond content of the polyurethane oligomer can be further regulated.

[0041] In some embodiments of the present application, the catalyst is selected from at least one of triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, zinc naphthenate, etc. Exemplarily, the catalyst is dibutyltin laurate. It should be noted that in the presence of dibutyltin laurate, the hydroxyl groups on the polyethylene glycol will preferentially react with the secondary aliphatic isocyanate groups on the diisocyanate, and the remaining isocyanate groups will react with the hydroxyl groups in the hydroxy acrylate, so as to ensure the successful chain extension of the reaction and obtain the polyurethane oligomer.

[0042] In some embodiments of the present application, the polymerization inhibitor is not particularly limited, such as at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

[0043] In some embodiments of the present application, the steps of preparing the polyurethane oligomer include:

[0044] Step (21): add diisocyanate, catalyst and solvent into a reaction kettle, then add diol, and keep warm for 0.5h to 2h after adding diol, and control the reaction temperature at 40°C to 50°C.

[0045] Specifically, diisocyanate, catalyst and solvent B are first added to the reaction kettle, and then diol is slowly added dropwise for reaction, the addition time is 1.5h to 3h, and after the addition is completed, the reaction is kept warm for 0.5h to 2h, and the reaction temperature is controlled at 40° C. to 50° C. The solvent B is not particularly limited, such as at least one of ethyl acetate, butyl acetate, acetone, butanone, etc.

[0046] Step (22) Add hydroxy acrylate and polymerization inhibitor into the reaction kettle, keep the temperature for 5 to 10 hours after the addition, and raise the temperature to 50° C. to 65° C. until the reaction is completed.

[0047] Specifically, continue to drop hydroxy acrylate and polymerization inhibitor into the reactor for 0.5 to 1 hour. After the dropwise addition, keep the reaction warm for 5 to 10 hours. Raise the reaction temperature to 50°C to 65°C. After the reaction is completed, check whether the reaction is complete and cool the mixture to discharge.

[0048] In some embodiments of the present application, the step of heating the temperature to 50°C to 65°C until the reaction is complete includes: taking the reaction solution for infrared analysis at intervals, and determining the completion of the reaction based on the characteristic peaks. Specifically, taking the reaction solution for infrared analysis, if there is no 2240cm -1 If a peak appears near the reaction solution, the reaction is considered complete, or the reaction solution is taken for -NCO value titration. If the titration result is ≤0.5%, the reaction is considered complete.

[0049] In some embodiments of the present application, the solid content of the polyurethane oligomer prepared in step (22) is 40% to 60%. It should be noted that the reaction method is also a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and gel effect. When the solid content is set within the range of 40% to 60%, the polymerization reaction rate is moderate, the viscosity is moderate, and the temperature is easy to control.

[0050] In some embodiments of the present application, the UV viscosity-reducing adhesive includes an acrylate resin, a thermal curing agent, a photoinitiator and the polyurethane polymer. By mass, the acrylate resin: the polyurethane polymer: the thermal curing agent: the photoinitiator is (60 to 80): (18 to 38): (0.5 to 1): (0.8 to 1.8).

[0051] In some embodiments of the present application, the thermal curing agent is selected from one or more of an isocyanate curing agent and an amine curing agent. Further, the thermal curing agent is preferably an isocyanate curing agent.

[0052] In some embodiments of the present application, the photoinitiator is at least one of acetophenone, dibenzoyl ketone, benzil ketal, benzophenone, 1-hydroxy-cyclohexyl benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, and the like.

[0053] It should be noted that the acrylate resin in the application examples can be a commercially available acrylate resin, such as SGR-5117 (Fenghui Chemical) and TCA-9051D (Taichang Resin), or can be self-developed and prepared, which is not limited here.

[0054] In some embodiments of the present application, the synthetic raw materials of the acrylic resin include 60 to 70 parts of soft monomers, 20 to 30 parts of hard monomers, 5 to 15 parts of functional monomers, and 0.01 to 0.05 parts of initiators by mass. Further, the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; wherein the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60 to 70): (20 to 30): (0.5 to 1.5): (0.5 to 1.5): (6 to 9). In this embodiment, by preparing an acrylic resin of a specific composition, it is beneficial to further improve the adhesion of the UV viscosity-reducing adhesive before illumination, so that the adhesion of the UV viscosity-reducing adhesive before illumination is greater than 35N / 25mm, and can reach up to 48.9N / 25mm, and the adhesion after illumination is less than 0.8N / 25mm.

[0055] It should be noted that the combined effects of soft monomers, hard monomers and functional monomers affect the performance of the entire acrylic polymer, and the selection and ratio of different soft and hard functional monomers make the overall performance of the acrylic polymer different; therefore, people usually control the type and amount of soft and hard functional monomers of acrylic copolymers according to the required performance and use conditions. The acrylic polymer in this article is not the best formula and ratio, but mainly through the regulation of the formula to meet the required performance and adapt to the UV viscosity-reducing adhesive system, the interaction between the polymer chains is weak, and the mechanical properties are stable.

[0056] In some embodiments of the present application, the soft monomer includes at least one of isooctyl acrylate, butyl acrylate, isononyl acrylate, and ethyl acrylate.

[0057] In some embodiments of the present application, the hard monomer includes at least one of methyl methacrylate, isobornyl methacrylate, methyl acrylate, vinyl acetate, vinyl acetate, N-vinyl pyrrole, styrene, and acrylonitrile.

[0058] In some embodiments of the present application, the functional monomer includes at least one of hydroxyethyl acrylate, acrylic acid, β-acryloxypropionic acid, glycidyl methacrylate, and acrylamide.

[0059] It should be noted that the initiator in the present application is not particularly limited. For example, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diethylhexyl peroxydicarbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, sodium persulfate, ammonium persulfate, and the like.

[0060] In some embodiments of the present application, the weight average molecular weight of the acrylic resin is 350,000 g / mol to 750,000 g / mol.

[0061] The present invention also provides a method for preparing an acrylic resin, comprising the following steps:

[0062] Step (11) introducing protective gas into the reaction container.

[0063] Specifically, the reaction container is a five-necked flask, the protective gas is nitrogen, and the ventilation time is 5 min to 60 min.

[0064] Step (12) Add part of the monomer raw material into the reaction container and heat it to 65° C. to 70° C. to obtain a first reaction solution.

[0065] Specifically, a portion of the soft monomer, the hard monomer and the functional monomer are weighed and dissolved in the solvent A as a base material, added into a five-necked flask, and the stirrer is turned on and the temperature is increased.

[0066] Step (13) The first reaction solution obtained in step (12) is further heated to 70° C. to 75° C., and the remaining monomer raw materials and a portion of the initiator are added and reacted for 1 to 2 hours to obtain a second reaction solution.

[0067] Specifically, after the first reaction liquid is heated up, the remaining monomer raw materials (ie, soft monomers, hard monomers and functional monomers) and a portion of the initiator are dissolved in solvent A, and slowly added to the flask using a peristaltic pump. After the addition is completed, the reaction is carried out for about 1.5 hours to obtain the second reaction liquid.

[0068] Step (14) The second reaction liquid obtained in step (13) is further heated to 75° C. to 85° C., and the remaining initiator is added, and the reaction is continued until the monomer raw materials react completely, and then heating is stopped to obtain an acrylate resin for use.

[0069] Specifically, the remaining initiator is added dropwise to the second reaction liquid, and the reaction is continued for about 1.5 hours after the addition is completed. When the monomer raw materials are basically reacted, the heating is stopped to obtain the acrylic resin for use.

[0070] In some embodiments of the present application, the solid content of the acrylic resin prepared after step (14) is 35% to 50%. It should be noted that the reaction method is a solution polymerization reaction, and the solvent, as a carrier of the reaction, has a certain influence on the polymerization activity and the gel effect. When the solid content is set within the range of 35 to 50%, the polymerization reaction rate is moderate, the viscosity is moderate, the temperature is easy to control, the chain transfer effect is small, and it is convenient for subsequent use.

[0071] In some embodiments of the present application, the solvent A is not particularly limited. For example, the solvent A includes at least one of ethyl acetate, butyl acetate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate, dipropylene glycol ethyl ether acetate, and dipropylene glycol butyl ether acetate.

[0072] The embodiment of the present application also provides a UV anti-viscosity tape, which includes the above-mentioned UV anti-viscosity adhesive and a substrate film. Exemplarily, the substrate film is a PO substrate film.

[0073] The present application also provides a method for preparing a UV adhesive tape, comprising the following steps:

[0074] Step (31) provides UV viscosity-reducing adhesive solution.

[0075] Specifically, UV viscosity-reducing adhesive is added into a container, solvent A is added to adjust the viscosity, mixed evenly, and allowed to stand for defoaming to obtain adhesive solution. It should be noted that solvent A has been specifically described above and will not be repeated here.

[0076] Step (32) is to coat the UV viscosity reducing adhesive solution on the release film.

[0077] Specifically, a coating machine is used to evenly coat the adhesive on the release film. Exemplarily, the release film is PET.

[0078] Step (33) dries the release film coated with the UV viscosity reducing adhesive solution.

[0079] Specifically, the release film coated with UV viscosity-reducing adhesive is placed in an oven to dry the solvent at a temperature of 60°C to 100°C for 1 minute to 3 minutes, and then coated on the substrate film to obtain an adhesive tape. Exemplarily, the substrate film is one of EVA, PET, PO, and PVC, and more preferably, the substrate film is PO.

[0080] Step (34) is to put the above-mentioned tape into an oven for curing at a temperature of 40° C. to 70° C. for 24 h to 72 h. After curing is completed, a high peel strength UV anti-adhesive tape is obtained.

[0081] In some embodiments of the present application, the viscosity of the UV viscosity-reducing adhesive is 300 cps to 3000 cps, and more preferably, the viscosity is 500 cps to 1500 cps.

[0082] In some embodiments of the present application, the dry thickness of the glue layer is 10um to 30um, and more preferably, the dry thickness of the glue layer is 15um.

[0083] In some embodiments of the present application, the 180° peel strength of the UV-resistant adhesive tape at room temperature can reach more than 40N / 25mm, and the 180° peel strength after UV treatment is reduced to less than 0.3N / 25mm.

[0084] The UV adhesive tape in this application is further described below in conjunction with specific examples and experimental data.

[0085] Acrylate resin example 1 (Z11)

[0086] (1) Preparation of acrylic resin

[0087] Step 111: nitrogen was introduced into a five-necked flask for 30 min.

[0088] Step 112: 20.4 g of isooctyl acrylate, 6.9 g of methyl acrylate, 0.3 g of hydroxyethyl acrylate, 0.3 g of acrylamide, and 2.1 g of acrylic acid were dissolved in 60 g of ethyl acetate as a base material, added to a five-necked flask, stirred, and heated to 70° C. Then, 47.6 g of isooctyl acrylate, 16.1 g of methyl acrylate, 0.7 g of hydroxyethyl acrylate, 0.7 g of acrylamide, 4.9 g of acrylic acid, 0.1 g of azobisisobutyronitrile, and 30 g of ethyl acetate were slowly added dropwise, and the mixture was reacted for 3 hours after the addition was completed.

[0089] Step 113: Raise the temperature to 75° C., slowly drop 0.06 g of azobisisobutyronitrile and 30 g of ethyl acetate into the reaction bottle, and react for 1.5 hours after the dropwise addition.

[0090] Step 114: Raise the temperature to 80°C, slowly drop 0.04g of azobisisobutyronitrile and 30g of ethyl acetate into the reaction bottle, react for 1.5h after the dropwise addition, cool the material to obtain an acrylate resin for standby use, the acrylate resin solid content is 38%. The weight average molecular weight of the acrylate resin is 516000g / mol, and the glass transition temperature of the acrylate resin is -37°C.

[0091] Acrylate resin example 2 (Z12)

[0092] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 1.5:1.5:6. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 613000 g / mol, and the glass transition temperature of the acrylic resin is -40°C.

[0093] Acrylate resin example 3 (Z13)

[0094] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 61:30:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 599000 g / mol, and the glass transition temperature of the acrylic resin is -30°C.

[0095] Acrylate resin example 4 (Z14)

[0096] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 65:25:10 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:9. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 726000 g / mol, and the glass transition temperature of the acrylic resin is -27°C.

[0097] Acrylate resin example 5 (Z15)

[0098] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 553000 g / mol, and the glass transition temperature of the acrylic resin is -15°C.

[0099] Acrylate resin example 6 (Z16)

[0100] The difference between the embodiment 1 and the embodiment 1 is that in step 112, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate, acrylamide and acrylic acid) is 68:23:9 by mass, wherein the ratio of hydroxyethyl acrylate: acrylamide: acrylic acid is 0.5:0.5:8. The solid content of the prepared acrylic resin is 38%, the weight average molecular weight of the acrylic resin is 702000 g / mol, and the glass transition temperature of the acrylic resin is -28°C.

[0101] Acrylate resin Example 7 (Z17)

[0102] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (hydroxyethyl acrylate and acrylic acid) is 68:23:9; among which, the ratio of hydroxyethyl acrylate: acrylic acid is 1:8.

[0103] Acrylate resin Example 8 (Z18)

[0104] The difference from Example 1 is that in step 112, calculated by mass, the ratio of soft monomer (isopropyl acrylate): hard monomer (methyl acrylate): functional monomer (acrylamide and acrylic acid) is 68:23:9; wherein the ratio of acrylamide: acrylic acid is 1:8.

[0105] Polyurethane oligomer example 1 (Z21)

[0106] Step 121: First add 34.2g of diphenylmethane diisocyanate, 0.05g of triethanolamine and 12.415g of acetone into a reaction kettle, and then slowly add 15.4g of polyethylene glycol 200 and 30g of acetone dropwise for 1.5h. After the addition is complete, keep the reaction warm for 1h and control the reaction temperature at 45°C.

[0107] Step 122: Continue to drop 50.4 g of pentaerythritol triacrylate, 0.03 g of toluene diphenol and 15 g of acetone into the reactor for 0.5 h. After the addition is complete, heat to 60 °C and keep warm for 6 h. The reaction liquid has no 2240 cm -1 The peak is discharged near the mol / l, and the material is discharged after cooling to obtain a polyurethane oligomer for use. The weight average molecular weight of the prepared polyurethane oligomer is 980 g / mol, and the double bond content is 0.54 mol / 100 g.

[0108] Polyurethane oligomer example 2 (Z22)

[0109] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 39.8:17.9:42.2; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 19.67:8.59. The weight average relative molecular mass of the prepared polyurethane oligomer is 910 g / mol, and the double bond content is 0.38 mol / 100 g.

[0110] Polyurethane oligomer example 3 (Z23)

[0111] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.8:16.5:46.6; wherein the hydroxy acrylate includes pentaerythritol triacrylate and hydroxypropyl acrylate, and the ratio of pentaerythritol triacrylate: hydroxypropyl acrylate is 29.53:4.29. The weight average molecular weight of the prepared polyurethane oligomer is 950 g / mol, and the double bond content is 0.47 mol / 100 g.

[0112] Polyurethane oligomer example 4 (Z24)

[0113] The difference between the polyurethane oligomer and Example 1 is that, by mass, diphenylmethane diisocyanate is used to replace isophorone diisocyanate, and the ratio of diphenylmethane diisocyanate: polyethylene glycol 200: hydroxy acrylate is 36.9:14.7:48.3; wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 977 g / mol, and the double bond content is 0.57 mol / 100 g.

[0114] Polyurethane oligomer Example 5 (Z25)

[0115] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 31.7:21.4:46.8, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1100 g / mol, and the double bond content is 0.51 mol / 100 g.

[0116] Polyurethane oligomer Example 6 (Z26)

[0117] The difference between the polyurethane oligomer and Example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 35.4:15.9:48.5, wherein the hydroxy acrylate is pentaerythritol triacrylate. The weight average molecular weight of the prepared polyurethane oligomer is 1050 g / mol, and the double bond content is 0.58 mol / 100 g.

[0118] Polyurethane oligomer comparative example 1 (D21)

[0119] The difference between the polyurethane oligomer example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 40:18:42; wherein the hydroxy acrylate is hydroxybutyl acrylate.

[0120] Polyurethane oligomer comparative example 2 (D22)

[0121] The difference between the polyurethane oligomer embodiment 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 47.4:21.4:31.2; wherein the hydroxy acrylate includes hydroxyethyl acrylate and pentaerythritol triacrylate, and the ratio of hydroxyethyl acrylate: pentaerythritol triacrylate is 13.93:3.58.

[0122] Polyurethane oligomer comparative example 3 (D23)

[0123] The difference between the polyurethane oligomer example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 31:23.2:45.7; wherein the hydroxy acrylate is pentaerythritol triacrylate.

[0124] Polyurethane oligomer comparative example 4 (D24)

[0125] The difference between the polyurethane oligomer example 1 is that, by mass, the ratio of isophorone diisocyanate: polyethylene glycol 200: hydroxy acrylate is 34.2:15.4:50.4; wherein the hydroxy acrylate is pentaerythritol triacrylate.

[0126] The samples prepared in polyurethane oligomer Examples 1 to 6 and Comparative Examples 1 to 4 were characterized, and the test results are shown in Table 1.

[0127] Table 1

[0128]

[0129] Preparation of UV viscosity-reducing tape: Prepare UV viscosity-reducing adhesive liquid according to the raw material composition and ratio in Table 2. The specific process is: add acrylate copolymer, polyurethane oligomer, thermal curing agent, photoinitiator 1173 and appropriate amount of ethyl acetate into a cup according to a certain ratio, mix evenly, the viscosity is 1200cps, and stand to defoam. Use a coating machine to evenly coat the above UV viscosity-reducing adhesive liquid on the PET release film. Put it in an oven at 80℃ / 2min to dry the solvent, and then transfer it to the substrate film to obtain the tape. Then put the tape in an oven and cure it at 40℃ for 72h.

[0130] Table 2

[0131]

[0132]

[0133]

[0134] Experimental test:

[0135] Peel strength test before / after illumination: The test standard is GB / T2792-2014. The specific operation is to cut a 25mmx300mm tape sample and use a universal material testing machine to perform a 180° peel strength test.

[0136] Test whether it is detached from the base film under stretching conditions: visual inspection, the specific operation is to cut a 10mmx100mm sample, use a universal material testing machine, set the initial spacing to 50mm, the stretching speed to 200mm / min, stretch the sample to break, and observe whether there is debonding.

[0137] Residual adhesive test after light exposure: visual inspection, the specific operation is to observe whether there is any residual material on the substrate after the peeling force is measured after light exposure.

[0138] The UV adhesive tapes prepared in each experimental example in Table 2 were subjected to peel strength test before illumination, peel strength test before illumination, test on whether the tapes were detached from the base film under stretching conditions, and residual adhesive test after illumination. The test results are shown in Table 3.

[0139] Table 3

[0140]

[0141]

[0142] It can be seen from UV anti-viscosity tape Examples 1 to 16 and Comparative Examples 1 to 3 that adding the polyurethane polymer prepared in the examples of the present application to the UV anti-viscosity tape is beneficial to reducing the adhesion of the UV anti-viscosity tape after illumination, without residual adhesive, and improving the adhesion of the UV anti-viscosity tape before illumination.

[0143] It can be seen from the test results of Examples 1 to 6 and Examples 10 and 11 and Example 9 that the combination of acrylate resin and polyurethane polymer prepared in the examples of the present application is beneficial to further improve the adhesion of the UV anti-viscosity tape before illumination. The adhesion of the UV anti-viscosity tape before illumination is above 30N / 25mm, which is a significant improvement over the adhesion of UV anti-viscosity tapes on the market before illumination (generally around 20N / 25mm), and there is no debonding or residual glue.

[0144] Furthermore, from Examples 1 to 8 and Examples 12 to 16, it can be seen that the synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers; the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; and the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9), which is beneficial to further improve the adhesion of the UV anti-viscosity tape before illumination, so that the adhesion of the UV anti-viscosity tape before illumination is above 37N / 25mm.

[0145] In order to further study the effects of different substrate films and active monomers (also called active diluents) in UV anti-viscosity tapes on the performance of UV anti-viscosity tapes, different UV anti-viscosity tapes were prepared according to the compositions in Table 4. It should be noted that the active monomers in this application are active monomers that can undergo cross-linking reactions under light conditions, such as acrylate monomers.

[0146] Table 4

[0147]

[0148] The UV adhesive tapes prepared in each experimental example in Table 4 were subjected to peel strength test before illumination, peel strength test before illumination, test on whether the tapes were detached from the base film under stretching conditions, and residual adhesive test after illumination. The test results are shown in Table 5.

[0149] Table 5

[0150]

[0151] It can be seen from Table 5 that the substrate film has a great influence on the UV viscosity-reducing tape prepared in the examples of the present application. The use of the PO substrate film can significantly improve the peel strength of the UV viscosity-reducing tape in the examples of the present application before light exposure. In addition, it can be seen from Comparative Example 5 that although adding a certain amount of active monomer to the UV viscosity-reducing adhesive of the present application will lead to a decrease in the peel strength of the UV viscosity-reducing adhesive before light exposure, it is not conducive to reducing the peel strength after light exposure, and there is residual adhesive after light exposure.

[0152] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A polyurethane oligomer, characterized in that: The synthetic raw materials of the polyurethane oligomer include, by mass, 25 to 40 parts of diisocyanate, 10 to 20 parts of diol, 40 to 60 parts of hydroxy acrylate, 0.04 to 0.08 parts of catalyst, and 0.04 to 0.08 parts of polymerization inhibitor; the hydroxy acrylate includes pentaerythritol triacrylate.

2. The polyurethane oligomer according to claim 1, characterized in that The number of double bonds in the molecular structure of the polyurethane oligomer is greater than or equal to 4; and / or The polyurethane oligomer has a double bond content of 0.3 mol / 100 g to 0.6 mol / 100 g.

3. The polyurethane oligomer according to claim 1, characterized in that The weight average relative molecular mass of the polyurethane oligomer is 900 g / mol to 3000 g / mol.

4. The polyurethane oligomer according to claim 1, characterized in that The solid content of the polyurethane oligomer is 40% to 60%.

5. The polyurethane oligomer according to any one of claims 1 to 4, characterized in that The diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate and dicyclohexylmethane diisocyanate; and / or The diol is selected from at least one of polyethylene glycol, polypropylene glycol, ethylene oxide-propylene oxide copolymer, polytetramethylene glycol, polyester diol, and polycaprolactone diol; and / or The hydroxy acrylate further comprises at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and trimethylolpropane diacrylate; and / or The catalyst comprises at least one of triethanolamine, triethylenediamine, dibutyltin laurate, stannous octoate, cobalt octoate, lead octoate, and zinc naphthenate; and / or The polymerization inhibitor includes at least one of cuprous chloride, hydroquinone, toluene diol, p-hydroxyanisole and 2,6-di-tert-butyl-p-cresol.

6. A method for preparing a polyurethane oligomer, characterized in that: The preparation method comprises the following steps: Add diisocyanate, catalyst and solvent into the reaction vessel, then add diol, keep warm for 0.5h to 2h after adding diol, and control the reaction temperature at 40℃ to 50℃; Add hydroxy acrylate and polymerization inhibitor into a reaction container, keep warm for 5 to 10 hours after adding, and raise the temperature to 50 to 65° C. until the reaction is completed; wherein the hydroxy acrylate includes pentaerythritol triacrylate.

7. The preparation method according to claim 6, characterized in that: The step of heating the temperature to 50° C. to 65° C. until the reaction is completed comprises: taking the reaction solution for infrared analysis at intervals, and determining the completion of the reaction based on characteristic peaks; or The reaction solution was taken for -NCO value titration. If the titration result was ≤0.5%, the reaction was considered complete.

8. A UV anti-adhesive tape, characterized in that: The UV anti-viscosity tape comprises the polyurethane oligomer according to any one of claims 1 to 5 or the polyurethane oligomer obtained by the preparation method according to claim 6 or 7.

9. The UV adhesive tape according to claim 8, characterized in that: The UV anti-viscosity tape comprises a UV anti-viscosity adhesive and a substrate film. The UV anti-viscosity adhesive comprises an acrylate resin, a thermal curing agent, a photoinitiator and the polyurethane polymer. By mass, the acrylate resin: the polyurethane polymer: the thermal curing agent: the photoinitiator is (60 to 80): (18 to 38): (0.5 to 1): (0.8 to 1.8).

10. The UV adhesive tape according to claim 8, characterized in that: The UV viscosity reducing adhesive does not include reactive diluents or reactive monomers; and / or The synthetic raw materials of the acrylic resin include soft monomers, hard monomers and functional monomers; the functional monomers include hydroxyethyl acrylate, acrylamide and acrylic acid; wherein the soft monomer: the hard monomer: the hydroxyethyl acrylate: the acrylamide: the acrylic acid is (60-70): (20-30): (0.5-1.5): (0.5-1.5): (6-9); and / or The peel strength of the UV de-viscosity adhesive before irradiation is greater than 15N / 25mm, and the peel strength of the UV de-viscosity adhesive after irradiation is less than 2.5N / 25mm 。

Citation Information

Patent Citations

  • Adhesive composition and UV (ultraviolet) visbreaking cutting adhesive tape

    CN114517068A

Cited By

  • Single-component UV viscosity-reducing adhesive and preparation method thereof

    CN120988632A